2022
DOI: 10.3390/foods11131924
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins, Carotenoids and Chlorophylls in Edible Plant Leaves Unveiled by Tandem Mass Spectrometry

Abstract: Natural pigments are a quite relevant group of molecules that are widely distributed in nature, possessing a significant role in our daily lives. Besides their colors, natural pigments are currently recognized as having relevant biological properties associated with health benefits, such as anti-tumor, anti-atherogenicity, anti-aging and anti-inflammatory activities, among others. Some of these compounds are easily associated with specific fruits (such as blueberries with anthocyanins, red pitaya with betalain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 71 publications
0
8
0
4
Order By: Relevance
“…The color of plant leaves is determined by the pigments in the vacuoles of leaf cells, especially by the levels and ratios of chlorophyll, carotenoids, and anthocyanins ( Borges et al, 2022 ). Among these, carotenoids primarily contribute to the formation of yellow, orange, and red colors, whereas anthocyanins mainly result in red, pink, purple, and blue leaves ( Clara, 2022 ). In this study, we explored the variation in pigment accumulation and levels of gene expression at different developmental stages of D. cercidifolius var.…”
Section: Discussionmentioning
confidence: 99%
“…The color of plant leaves is determined by the pigments in the vacuoles of leaf cells, especially by the levels and ratios of chlorophyll, carotenoids, and anthocyanins ( Borges et al, 2022 ). Among these, carotenoids primarily contribute to the formation of yellow, orange, and red colors, whereas anthocyanins mainly result in red, pink, purple, and blue leaves ( Clara, 2022 ). In this study, we explored the variation in pigment accumulation and levels of gene expression at different developmental stages of D. cercidifolius var.…”
Section: Discussionmentioning
confidence: 99%
“…The different colors of plant organs depend on the relative content and distribution of the three types of pigments (chlorophyll, carotenoids, and anthocyanins) (Baek et al, 2012;Sousa, 2022). A previous study reported that a high ratio of anthocyanins relative to the other two pigments (chlorophyll and carotenoids) was detected in a colored-leaf cultivar of P. deltoides ('Caihong', CHP) (Zhuang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue samples selected for LM were then fixed, sliced, and stained for semithin section LM and TEM following the methodology described by Mesquita et al [ 16 ]. The concentration of sucrose, glucose, Quina cortisol, fructose, cellulose, lignin, starch, chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids in the frozen leaf samples from B untreated and B treated plants were analyzed using tandem mass spectrometry method described by C Sousa [ 17 ].…”
Section: Methodsmentioning
confidence: 99%